Effects of Hydrogen Sulfide at Normal Body Temperature and in the Cold on Isolated Tail and Carotid Arteries from Rats and TRPA1 Knockout and Wild-Type Mice - Leonardo Kelava; Eszter Pakai; Kazushi Ogasawara; Kata Fekete; Gabor Pozsgai; Erika Pinter; Andras Garami (Biomedicines)
Background: Hydrogen sulfide (H2S) is a gasotransmitter that modulates vascular tone, causing either vasodilation or vasoconstriction depending on the vascular bed, species, and experimental conditions. The cold-sensitive transient receptor potential ankyrin-1 (TRPA1) channel mediates H2S-induced effects; however, its contribution to the vasomotor responses of different arteries at different temperatures has remained unclear. Here, we aimed to fill this gap by comparing the effects of sodium sulfide (Na2S), which is a fast-releasing H2S donor, on the isolated carotid and tail skin arteries of rats and mice at cold and normal body temperature with wire myography. Under the same circumstances, we also aimed to compare the effects of the canonical endothelium-dependent and -independent vasodilators, acetylcholine and sodium nitroprusside, respectively. Methods: We isolated the carotid and tail arteries from 32 adult Wistar rats and 64 TRPA1 knockout and wild-type mice, and then we studied their vasomotor responses to increasing doses (10−6–10−3 M) of Na2S as well as to acetylcholine and sodium nitroprusside (10−5 M for both) at 37 °C and in cold (17 or 20 °C). Results: In rat vessels, Na2S caused constriction of the carotids and relaxation of the tail arteries, which were not influenced by temperature. In mouse carotids, Na2S caused vasorelaxation, which was more pronounced in the cold at a lower dose (10−4 M). At a higher dose (10−3 M), the dilation was markedly attenuated in the absence of the TRPA1 channel. In the mouse tail arteries, Na2S caused vasorelaxation at 37 °C and vasocontraction in the cold. The genetic blockade of TRPA1 channels did not influence the vasomotor responses of the mouse tail arteries. Sodium nitroprusside-induced vasorelaxation was not influenced by any of the investigated factors, while acetylcholine-induced dilation decreased in the cold in all vessel types. Conclusions: Our results reveal the function of TRPA1 in the H2S-induced dilation of carotid arteries in mice. We also highlight interspecies differences in the vasomotor responses between rats and mice, as well as the importance of the effect of temperature on vascular responses. The implementation of the identified variables in future research can advance our understanding of cardiovascular physiology, especially in conditions with hypothermia (either accidental or therapeutic).